Analisis Pusat Pertumbuhan Ekonomi Pada Tingkat Kecamatan di Kabupaten Asahan Sumatera Utara - Herman Cahyo D; Leni Kunia Optari; Duwi Yunitasari Duwi Yunitasari (MediaTrend, 2021)
One of the regional development strategies that became the focus of this research was the determination of the growth center. This study aims to find out the areas that are the growth in Asahan Regency and the highest relationship between spatial interactions between the growth centers and the hinterland. This analysisi tool used area scalogram, centrality index, and gravity index.. The results showed that the area that had a hierarchy with a high upward categorization as the center of growth was Kecamatan Kisaran Barat. Kisaran Barat as the growth center with the hinterland region which has the highest interaction value is the Kisaran Timur District, Air Joman District, and Pulo Bandring District.